2014
DOI: 10.1002/2013jd021129
|View full text |Cite
|
Sign up to set email alerts
|

Separation of ash and sulfur dioxide during the 2011 Grímsvötn eruption

Abstract: Modeling the transport of volcanic ash and gases released during volcanic eruptions is crucially dependent on knowledge of the source term of the eruption, that is, the source strength as a function of altitude and time. For the first time, an inversion method is used to estimate the source terms of both volcanic sulfur dioxide (SO 2 ) and ash. It was applied to the explosive volcanic eruption of Grímsvötn, Iceland, in May 2011. The method uses input from the particle dispersion model, FLEXPART (flexible parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
101
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 91 publications
(112 citation statements)
references
References 77 publications
11
101
0
Order By: Relevance
“…9g retrieved 12 h later, ash is detected to the east of Iceland that had been released before 12 h prior, demonstrating the difficulty of retrieving the opaque ash clouds close to Iceland. For this retrieval, there is also no ash detected over Europe, even though ash was observed over Europe at this time (Pappalardo et al, 2013). The exemplary results in Fig.…”
Section: Forecast Model Results Compared To Satellite Observationsmentioning
confidence: 62%
See 2 more Smart Citations
“…9g retrieved 12 h later, ash is detected to the east of Iceland that had been released before 12 h prior, demonstrating the difficulty of retrieving the opaque ash clouds close to Iceland. For this retrieval, there is also no ash detected over Europe, even though ash was observed over Europe at this time (Pappalardo et al, 2013). The exemplary results in Fig.…”
Section: Forecast Model Results Compared To Satellite Observationsmentioning
confidence: 62%
“…Eckhardt et al (2008) showed that a posteriori calculated with no emission in the a priori emission gave similar results to a posteriori calculated with estimated emissions in the a priori. A posteriori estimates are also calculated with low ash emissions in the a priori estimates in the Moxnes et al (2014) and Kristiansen et al (2015) studies. An a priori emission with ash is considered more conservative due to undetected ash.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the Grímsvötn (2011) eruption the 3-D ash clouds estimated by Moxnes et al (2014) using Flexpart combined with optimized emissions based on inversion modelling with IASI measurements, were used as input to the radiative transfer simulations. The ash particles were assumed to be composed of andesite, and the refractive index was taken from Pollack et al (1973).…”
Section: Simulation Of Infrared Seviri Imagesmentioning
confidence: 99%
“…Kristiansen et al, 2012;Moxnes et al, 2014;Pelley et al, 2015;Stohl et al, 2011). In this way, Kristiansen et al (2012) estimated optimal volcanic ash source terms for the Eyjafjallajökull eruption using an inversion algorithm with satellite-retrieved ash column loadings, a number of 10 emission scenarios and two atmospheric dispersion models.…”
mentioning
confidence: 99%